To solve the two-step equation [tex]\( 14 = 31.7 - 3x \)[/tex], we'll follow these steps:
Step 1: Isolate the term involving [tex]\( x \)[/tex].
- To do this, we need to move all the constant terms to the other side of the equation. We can start by subtracting 31.7 from both sides of the equation:
[tex]\[ 14 - 31.7 = 31.7 - 3x - 31.7 \][/tex]
Simplifying the left side, we get:
[tex]\[ -17.7 = -3x \][/tex]
Step 2: Solve for [tex]\( x \)[/tex].
- Now we need to isolate [tex]\( x \)[/tex] by dividing both sides of the equation by -3:
[tex]\[ \frac{-17.7}{-3} = x \][/tex]
Simplifying the division, we get:
[tex]\[ x = 5.9 \][/tex]
So, the solution to the equation [tex]\( 14 = 31.7 - 3x \)[/tex] is:
[tex]\[ x = 5.9 \][/tex]